Establishment Of The Callus And Cell Suspension Cultures For The Growth Of Pogostemon Cablin - Che Saad, Norlia (2014)
In this study, plant cell culture technique was used in order to investigate the production of patchouli alcohol in callus and cell suspension cultures. The callus cultures were induced from the intact Pogostemon cablin leaves called explants. Different types, concentration of plant growth regulators (PGRs) and different culture conditions (light, carbon source and inoculum size) were studied in order to produce a rapid-growing callus cultures and well-dispersed cell suspension cultures or P. cublin. The best condition for callus cultures growth was obtained in the Murashige and Skoog (MS) basal medium containing I mg/L picloram (MS I d) which was maintained in the dark for 21 days. Callus cultures were healthy with whitish and friable features. However, the cultured explants showed negative response to MS medium supplemented with 2, 4- D and all combination of picloram and 2, 4-0. The healthy, fast growing and friable callus cultures were then used to establish the cell suspension cultures. Under the influences of different concentrations and combinations of PGRs and light, rapid growth of cell suspension cultures were observed in the MDI medium.